THE AUTOMATIC REPRESENTATION OF THE OVAL WHEN ONE OF ITS RADII - Liviu Pruna; Andrei Slonovschi (Journal of Industrial Design and Engineering Graphics)
In technical drawing, an oval is defined as a closed plane curve formed by arcs of circles that connect smoothly. This type of curve is rarely used in technical drawing, and there is no specific command for representing it in CAD drawing software. Therefore, in this paper, the authors propose a new AutoCAD command that automatically sketches an oval based on the provided data. They present, explain, and discuss the command's theoretical foundation.